Lower back pain in young climbers: a retrospective cross-sectional study - Carraro, A.; Gilic, B.; Bertolo, R.; Albergoni, A.; Sarto, F.; Roklicer, R.; Sarto, D. (Frontiers in Physiology, 2023)
Objective The popularity of sport climbing has been growing since its inclusion in the Olympic Games program, which led to more people practicing it on recreational, amateur, and professional levels. Strenuous climbing training sessions and competitions might lead to frequent and serious musculoskeletal injuries and complaints among competitive climbers. This study aimed to investigate the prevalence of low back pain (LBP) and to explore the influence of various risk factors on LBP in adolescent climbers.